Model income tax treaties : a comparative presentation of the texts of the model double taxation conventions on income and capital of the OECD (1963 and 1977), United Nations (1980), and United States (1981) /: a comparative presentation of the texts of the model double taxation conventions on income and capital of the OECD (1963 and 1977), United Nations (1980), and United States (1981). (1990) - Unknown
No abstract available